Generation of reactive oxygen and nitrogen species in pea cultivars under copper exposure - Lehotai, Nóra (Acta Biologica Szegediensis, 2011)
Copper is an essential microelement in plants, but its exposure can induce toxicity symptoms such as growth inhibition, chlorosis or necrosis. The aim of this study was to investigate the physiological responses of two pea cultivars (Pisum sativum L. cv. Rajnai törpe and cv. Lincoln) to long term copper exposure. Seven-day-old pea plants were treated with 25 or 50 μM CuSO4, in nutrient solution for 14 days. We studied the growth parameters, the metal uptake, the levels of different reactive oxygen species (hydrogen peroxide, H2O2 and superoxide radical, O2.-) and reactive nitrogen species (nitric oxide, NO. and peroxynitrite, ONOO-) together with lipid peroxidation and cell death in the meristem cells of pea roots using in vivo and in situ microscopic methods. Long-term copper exposure resulted in a serious decrease in shoot and root growth of both pea cultivars and the root system proved to be more sensitive to the stressful condition. The reason of higher sensitivity of the root system is that the largest proportion of copper accumulated in it, namely, pea plants exclude the toxic metals from their shoot. Copper treatment induced the elimination of O2.- and the concurrent H2O2 generation in root tips of both cultivars. The level of NO significantly decreased as the effect of Cu2+ exposure, while the level of ONOO- (+OH.) enhanced, suggesting the occurrence of the reaction between O2.- and NO yielding peroxynitrite. As the effect of copper, lipid peroxidation and cell death were detected in the root tips which led to growth inhibition and biomass decrease of pea plants.